Structural characterization and immunostimulatory activity of a water-soluble polysaccharide from abalone (Haliotis discus hannai Ino) muscle - Linfan Shi; Gengxin Hao; Jun Chen; Junling Wang; Wuyin Weng (Food Science and Human Wellness, 2023)
A water-soluble polysaccharide from abalone muscle (AMPP) was isolated. The contents of carbohydrate, protein, uronic acid, and sulfate in AMPP were 83.5 %, 0.5 %, 2.7 %, and 2.6 %, respectively. High-performance liquid chromatography analysis indicated that AMPP was homogeneous and had an average molecular weight of approximately 3.2 kDa. The main monosaccharides of AMPP were glucose (Glc) and mannose with a molar ratio of 99.7:0.3. The structural characteristics of AMPP were elucidated through methylation analysis, Fourier transform infrared spectroscopy, and nuclear magnetic resonance spectroscopy. The linkages of AMPP consisted of terminal, 1,4-linked, 1,6-linked, and 1,4,6-linked Glcp with a molar ratio of 3.1:7.2:1.0:2.5. In one repeat unit of the proposed AMPP structure, the backbone chain was composed of eight 1→4 glycosidic bonds and one 1→6 glycosidic bond, with three branch chains linked by 1→6 glycosidic bond. In addition, AMPP was found to possess potent immunostimulatory activity via rising phagocytosis of RAW264.7 cells and promoting secretion of TNF-α.